Effect of optimized formulation (combination of bronopoland kathon)on compositional andphysico-chemical parameters of milk samples - Mitul, Bumbadiya; Singh, Richa; Arora, Sumit; Mann, Bimlesh; Rao, Priyanka Singh (Indian Journal of Dairy Science, 2021)
The experiment was conducted to study the effect of prepared optimized preservative formulation (combination of bronopol and kathon) on compositional and physico-chemical parameters of milk. The optimized formulation was added at the rate of 0.6% in milk samples and effect was observed on estimation of fat, protein, lactose and ash content during storage at 37oC. For comparison, the legally permitted preservative (by Food Safety and Standard Authority of India, 2011) formalin was also added at the rate of 0.4% in milk samples. There was no significant effect of optimized formulation on estimation of fat and lactose content for 45 days and total solid (TS), ash and protein content for 90 days. However, on addition of formalin, the fat and lactose values of milk decreased after 15 days of storage and no significant effect was observed on TS, ash, protein content for 90 days and lactose content for 60days.